Problematika Pembelajaran Mahasiswa Lulusan Sekolah Umum pada Program Studi Pendidikan Bahasa Arab di Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta - Nanda Pratama; Muhammad Syafii Tampubolon; Khanafi Khanafi (Yayasan Azhar Amanaa Yogyakarta, 2022)
This study aims to determine the problems of learning Arabic, especially for students of Arabic Language Education (PBA), from public schools who continue their education at the Tarbiyah Madani College of Yogyakarta. Learning Arabic has become one of the important subjects in education in Indonesia, from elementary to tertiary level. One of them is at the STIT Madani Yogyakarta college. Where students who continue their education at the lecture level can take the Arabic Language Education study program at STIT Madani Yogyakarta. Those with different backgrounds graduate from both ma'had-ma'had or Islamic boarding schools, Madrasah Aliyah and also other public schools such as SMA/SMK where they have big hopes and aspirations by continuing their education. The types of problems faced by students in the learning process in class include: 1) Vocabulary/mufroda problems, 2) Qowaid and i'rob problems, 3) Tarqib/word order, 4) Shame and lack of confidence. This type of research is a quantitative descriptive. Data collection techniques were carried out based on observation, interviews, experience, and the author's observations. The results of this study indicate that there are two factors, namely supporting factors and inhibiting factors, supporting factors are something that can facilitate and maximize the target of what has been determined, while inhibiting factors are everything that can complicate and support the failure of STIT Madani Yogyakarta students in the learning process